An Advanced Compiler Designed for a VLIW DSP for Sensors-Based Systems - Hu He; Xu Yang (Sensors, 2012)
The VLIW architecture can be exploited to greatly enhance instruction level parallelism, thus it can provide computation power and energy efficiency advantages, which satisfies the requirements of future sensor-based systems. However, as VLIW codes are mainly compiled statically, the performance of a VLIW processor is dominated by the behavior of its compiler. In this paper, we present an advanced compiler designed for a VLIW DSP named Magnolia, which will be used in sensor-based systems. This compiler is based on the Open64 compiler. We have implemented several advanced optimization techniques in the compiler, and fulfilled the O3 level optimization. Benchmarks from the DSPstone test suite are used to verify the compiler. Results show that the code generated by our compiler can make the performance of Magnolia match that of the current state-of-the-art DSP processors.